Obstetric Fistula: Existing Challenge of Developing Countries - Kattel, Pramod (Nepal Journal of Obstetrics and Gynaecology, 2018)
Developing countries are the home ground of obstetric fistula. It is usually the result of injury following childbirth or its consequences. The most common type of obstetric fistula is vesico-vaginal. Neglected obstructed labour is considered as the major etiology. Persistent leakage of urine is the most common presentation. It usually develops 3 to 14 days following childbirth. It degrades the quality of life of females. It may lead to medical, social, economic and psychological effects on reproductive age females. It is the marker to determine the quality of health system of any country. Proper use of partograph and timely intervention decreases its prevalence. History, examination and dye test are usually taken as main diagnostic tools in resource poor settings. It is a treatable condition at usual times. Social awareness regarding fistula is the need of developing countries. Drink, Dry and Drain are the key parameters of fistula repair success. Social rehabilitation following surgical repair is of prime importance.